Simulação física da ZTA de aços inoxidáveis lean duplex 2101 e 2404 em sistema Gleeble®: evolução microestrutural e resistência à corrosão - Kugelmeier, Cristie Luis (Universidade Federal de São Carlos, 2022)
In this study, physical simulations of welding thermal cycles were performed to evaluate the microstructural evolution and corrosion resistance of the heat-affected zones (ZTAs) of lean duplex stainless steels (LDSSs) 2101 and 2404 using the Gleeble® thermomechanical system. The simulations were performed under two conditions: i) peak temperature of 1350 °C, dwell time of 3 seconds, cooling rates of 200, 100, 50, 20 and 10 °C/s up to 800 °C and subsequent cooling to room temperature; and ii) peak temperature of 1050 °C, dwell time of 120 seconds and cooling rates of 5 and 1 °C/s with cooling to room temperature. The results obtained show that the cooling rates of 200 to 10 °C/s caused microstructural changes with the formation of different austenite morphologies, while for the rates of 5 and 1 °C/s the microstructures were composed of ferrite and austenite phases. The cooling rates of 200 and 100 °C/s were the conditions where both materials showed the highest presence of Cr nitrides and carbides. Although the precipitation of deleterious phases occurred, the degree of Cr depletion remained below 1%, except for the 200 °C/s cooling rate of LDSS 2404. For LDSS 2101, the resistance to pitting corrosion was lower, with a narrow passive range, while LDSS 2404 showed resistance to pitting corrosion with a passive range greater than 1000 mVAg/AgCl. The results obtained for both materials showed that the precipitation of Cr nitrides and carbides did not cause significant changes in the localized corrosion behavior.
Physical simulation of the HAZ of lean duplex stainless steels 2101 and 2404 in a Gleeble® system: microstructural evolution and corrosion resistance
Keywords: Lean duplex stainless steel 2404; Physical simulation of thermal cycles; Heat-affected zone; Cooling rates; Microstructure evolution; Pitting corrosion resistance; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA FISICA